Factors associated with HIV/AIDS sexual risk among young women aged 15-24 years in Nigeria - Chinekwu A. Obidoa; Cyr E. M'Lan; Stephen L. Schensul (AOSIS, 2012)
The growing rate of sexual risk-taking among young people contributes significantly to the spread of the HIV/AIDS epidemic in Nigeria. This study, explores the influence of socio-demographic, HIV/AIDS awareness and female empowerment on the sexual risk behaviors of unmarried Nigerian women aged 15-24. The data presented in this paper was drawn from the 2003 Nigeria National Demographic and Health Survey. The sample consisted of unmarried women aged 15-24 in the dataset. Data was collected through a structured and interviewer administered questionnaire. Multivariate logistic regression models were used to identify the most important predictors of sexual risk behaviors. Sexual risk-taking is relatively high among unmarried young women. Among those who are sexually active, 80% indicated that they did not use a condom during their first sexual encounter. Regression analysis revealed that younger age, lower HIV/AIDS prevention and transmission knowledge, lower knowledge of where to obtain condoms, lower material standard of living and greater intimate partner violence were significantly associated with sexual risk-taking in this population. Findings revealed that the sexual behavior of unmarried Nigerian women aged 15-24 is influenced by a complex matrix of factors. Identifying specific processes and contexts that promote the concentration of risk among sub-sections of young unmarried women aged 15-24 years in Nigeria should be a research and intervention priority.